Reducing greenhouse gas emissions: using community-based social marketing to identify targets for behavior change - Ross, Elizabeth C., author; Aloise-Young, Patricia, advisor; Witt, Jessica, committee member; Long, Marilee, committee member; Tompkins, Sara Anne, committee member (Colorado State University. Libraries, 2022)
Greenhouse gas emissions produced by human activities threaten all life on earth. Project Drawdown (2020), Wynes and Nicholas (2017), and other similar efforts have catalogued behaviors that individuals can adopt to stall and mitigate climate change. Thus far, no empirical attempts have been made to determine which of these behaviors make viable targets for behavior change interventions. The current study remedies that gap through the use of community-based social marketing (CBSM), which distinguishes behavioral targets using the behaviors' probability, penetration, impact, and barriers. Following the CBSM framework, penetration and probability were assessed for 16 low-carbon behaviors to find those with the lowest adoption rates (i.e., penetration) and the highest likelihood of being adopted (i.e., probability). Impact for each behavior was also estimated using Project Drawdown and other similar sources. The perceived barriers and benefits of behavior engagement were then assessed for the five behaviors with the most ideal combination of impact, penetration, and probability: living motor vehicle free, purchasing green energy credits, following a plant-based diet, avoiding a plane flight, and installing compact fluorescent lamp (CFL) and light-emitting diode (LED) bulbs. Recommendations for future interventions aimed at reducing greenhouse gas emissions were then made based on the findings pertaining to these five behaviors. Among the target audience considered in this work, very few individuals had purchased green energy credits. Additionally, the barriers to purchasing green energy credits had clear solutions for many participants. Given the comparable ease with which participants can engage in this behavior, I recommend that future interventions target the purchasing of green energy credits. Additional recommendations are made for the five behaviors, considering the benefits and challenges associated with each one.
Keywords: community-based social marketing; behavior change; greenhouse gas emissions